Evaluation of image quality in cervical spine lateral radiographs - Shrestha, S; Maharhan, S; Khanal, U; Humagain, M (Journal of Chitwan Medical College, 2017)
In diagnostic radiography, cervical lateral spine x-ray is common radiographic examination among imaging of cervical spine. Thus, it is important to show entire anatomical structure, adequate penetration, soft tissue of neck and bony detail. This study attempts to quantify the quality of cervical spine radiographs by evaluating the quality of depiction of the anatomical and physical details. In this cross-sectional study, about 188 cases of cervical spine lateral radiographs were collected for study over the three months of period. Nine image criteria i.e. anatomical coverage, soft tissue visualization, C7/T1 junction, sharp bony detail, proper chin raise, artifact, density, patient rotation and collimation were followed and tabulated. Obtained data were analyzed using in SPSS v.20 software and shown in frequency, percentages, bar diagrams and graphs. Among 188 patients, about 23.4% cervical radiographs met all image criteria but remaining 76.6% did not meet these criteria due to no anatomical coverage (33.5%), no proper chin raise (46.3%), artifact (13.3%), patient rotation (50%) and no collimation (33.5%). It is difficult to perform good quality cervical radiograph according to European guidelines14. To a great extent the quality of cervical radiographs depends upon skill of radiographer, equipment condition (x-ray machine, CR reader) and co-operation of patients. This is always a challenge for radiographer and technologist.